Ups and Downs in 75 Years of Electrocochleography - Eggermont, Jos J. (Frontiers in Systems Neuroscience, 2017)
Before 1964, electrocochleography (ECochG) was a surgical procedure carried out in the operating theatre. Currently, the newest application is also an intra-operative one, often carried out in conjunction with cochlear implant surgery. Starting in 1967, the recording methods became either minimal– or not–invasive, i.e., transtympanic or extra tympanic, and included extensive studies of the arguments pro and con. I will review several valuable applications of ECochG, from a historical point of view, but covering all 75 years if applicable. The main topics will be 1) comparing human and animal cochlear electrophysiology, 2) the use in objective audiometry involving tone pip stimulation—currently mostly pre cochlear implantation but otherwise replaced by auditory brainstem response (ABR) recordings, 3) attempts to diagnose Ménière’s disease and the role of the summating potential, 4) early use in diagnosing vestibular schwannomas—now taken over by ABR screening and MRI confirmation, 5) relating human electrophysiology to the effects of genes as in auditory neuropathy, and 6) intracochlear recording using the cochlear implant electrodes. The last two applications are the most recently added ones. The ‘historical aspects’ of this review will highlight the founding years prior to 1980 when relevant. A survey of papers on Pubmed shows several ups and downs in the clinical interest as reflected in the publication counts over the last 75 years.